Corporate Governance and its Role in Performance Improvement and Reducing Fraud in Islamic Banking - Leila Zamanianfar; Mohammad Reza Mahdyar Ismaili (تحقیقات مالی اسلامی (پیوسته))
In general, good and appropriate corporate governance in banks is considered one of the most important tools to prevent fraud and corruption. Investigations indicate that in various countries, despite the weakness of corporate governance, corruption and financial fraud have increased, and as a result, the performance of banks has decreased. On the other hand, the issue of corporate governance has attracted the attention of economic and accounting professionals in recent decades, and in many countries, strict regulations have been established to improve corporate governance in Islamic banking. The question raised in the present study is whether it is possible to maintain and improve the financial performance of Iranian banks and reduce fraud by using corporate governance procedures. This article is compiled with the aim of reviewing the theoretical foundations and existing research literature on good corporate governance and its role in improving performance and reducing fraud in Islamic banking. The research method is based on promotion and dissemination as well as summarizing and inferring the topics and ideas of other researchers. In this article, an attempt is made to present the theoretical and scientific foundations of corporate governance, performance improvement, fraud and the importance of the Sharia Supervisory Board. Surveys indicate that interest-free banking requires a regulatory structure and corporate governance, and the creation of a suitable and strong corporate governance mechanism will probably motivate banks to participate in economic activities and financing in a more appropriate way. Also, the implementation of corporate governance is a solution to prevent fraud and finally, corporate governance significantly affects the performance of Islamic banks.